Silat in Transition: Integrating Sports Science, Culture, and Competition into a Unified Coaching Framework - Mohamad Nizam Mohamed Shapie; Mohamad Rahizam Abdul Rahim; Nagoor Meera Abdullah; Hazim Samsudin; Nasru Syawai Nawai; Nurul Ihsan; Padli Padli (Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2026)
This paper examines the transformation of Silat within the Seni Silat Malaysia curriculum through a systematic synthesis of research conducted by Universiti Teknologi MARA (UiTM) from 2013 to 2024. Based on the analysis of 47 peer-reviewed studies, the study traces how Silat has evolved from a traditionally rooted martial art into an interdisciplinary domain integrating sports science, pedagogy, and cultural identity. Using a matrix-based systematic review supported by text-mining techniques, three developmental phases were identified. The first phase (2013–2016) focused on physiological profiling and baseline performance indicators. The second phase (2017–2020) marked a transition toward applied sports science, including training methodologies, coaching strategies, and curriculum integration. The third phase (2021–2024) emphasized interdisciplinary collaboration and international alignment, particularly through the establishment of the AIRBORNE Research Interest Group. Across these phases, five core domains emerged: physical performance, sports-specific training, curriculum integration, recovery strategies, and socio-cultural identity. These domains collectively underpin a unified coaching framework that balances evidence-based practice with cultural authenticity. The emergence of Silat Tempur and its evolution into the Silat EVO competition model demonstrate a clear pathway of research translation into practice. This progression highlights how academic inquiry informs competition design, coaching competencies, and athlete development systems. The findings position Silat as a dynamic martial art in transition, offering a replicable model for integrating tradition, science, and competitive innovation in global martial arts development.